PENINGKATAN KUALITAS PEMBELAJARAN MELALUI MODEL PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) TIPE TEAM GAMES TOURNAMENT DI KELAS II SDN CEMPAKA PUTIH BARAT 03 JAKARTA PUSAT - Sri Melati; Dudung Amir Soleh; Mustafid (STKIP Subang, 2023)
This study aims to describe the improvement in the quality of learning through cooperative learning models (Team Games and Tournaments) type of Cooperative Learning (TGT). This research is included in the class action research (CAR). The research subjects were 31 class IIA students with the object of research being the quality of learning. The technique for collecting data in this research is observation and documentation. The data collected is in the form of a questionnaire and a Likert scale. The results of this study indicate an increase in the quality of learning using cooperative learning models (Cooperative Learning) Team Games and Tournament (TGT) types. This can be proven by the average indicator of acquiring teacher skills scores, namely in cycle I the first meeting was 64.66% and the second meeting was 79.77%. While cycle II the first meeting averaged 86.15% and the second meeting was 93.85%. Meanwhile, the average acquisition value of student learning activities in the first cycle of the first meeting was 53.33% and the second meeting was 93.33%.